(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Hospital-acquired pneumonia (HAP) is a significant morbidity, mortality and increasing healthcare cost associated with gram-negative pathogens. Conventional intravenous (IV), last-resort colistin is limited by its systemic toxicity and lack of lung tissue penetration. In contrast, inhaled colistin provides targeted pulmonary delivery to limit exposure beyond the opposite lung, hence improving therapeutic efficacy over the systemic effects. Methods: As a prospective, randomized, controlled trial, adult patients in the age group of 18 to 65 years suffering from culture-confirmed gram-negative HAP were enrolled at JPMC, Karachi, over January 2025 to June 2025.For 14 days, there were 80 patients randomized to two equal groups (n = 80 each) who were given either IV or inhaled colistin sodium (2 million international units three times daily by jet nebulization). Clinical cure was defined as the complete resolution of pneumonia signs and symptoms with radiographic improvement and no additional antibiotics. Microbiological eradication, 28 days, all cause mortality and incidence of adverse events, especially nephrotoxicity, were secondary endpoints that were studied. The sample size was determined to have 80% power and an alpha value of 0.05, assuming the inhaled clinical cure rate to be 59% and the IV clinical cure rate to be 37%. Analyses of the data were carried out in SPSS v26 with Chi square tests for categorical variables and t tests or Mann-Whitney U tests for the continuous variables. Results: In comparison with the IV group, the clinical cure rate to the inhaled colistin group was significantly higher (62.5 % vs. 37.5%, p = 0.004) and the microbiological eradication rate (56.3 % vs. 31.3%, p = 0.006). Additionally, 28-day mortality was decreased in the inhaled group (15.0% vs. 30.0%, p = 0.03). Compared to the inhaled group, 1 of those receiving IV colistin developed nephrotoxicity (8.8%), while 1 of patients in the IV colistin group developed nephrotoxicity (2.5%) (p = 0.04). Subgroup analyses of other subsets did not indicate the benefit of inhaled colistin dependent on mechanical ventilation status or the presence of comorbidities. Conclusion: In patients with gram-negative HAP, clinical and microbiological outcomes are superior and the safety profile is better for inhaled colistin than for IV administration. These results support the adoption of nebulized colistin into protocols of treatment for patients at risk of systemic side effects and when an increase in lung tissue penetration is desired.